THE USE OF THE CASE STUDY METHOD IN TEACHING THE TOPIC OF HYDROCARBONS - Kutlimuratova, Shakhnoza Aralbayevna; Aytbaeva, Hurliman Berdakhovna; Aymurzaeva, Liza Gulmurzaevna (SCIENCE and SOCIETY, 2026)
The article examines the use of the case study method in teaching the topic of hydrocarbons, which is one of the important sections of chemistry in the system of general secondary education. The pedagogical potential of the case study method, its role in the educational process, and its significance in developing students’ analytical thinking are analyzed.
Keywords: pedagogical technology; case study; problem situation; hydrocarbons; petroleum products; natural gas; plastics; synthetic fibers; rubber